Catalase Activity Expression in Patients with Plasmodium vivax Malaria - Bilgin, R.; Yalcin, M.S.; Kilic, E.; Kaya, E.; Yazar, S.; Koltas, I.S. (Asian Journal of Chemistry, 2012)
Plasmodium vivax (P. vivax) causes the most geographically widespread human malaria. It infects mainly the reticulocytes. Free radicals and related species have attracted a great deal of attention in recent years. They are mainly derived from oxygen and is generated in our body by various endogenous systems, exposure to different pathophysiological states. Catalase seems to be the main regulator of hydrogen peroxide metabolism. Hydrogen peroxide at high concentrations is a toxic agent, while at low concentrations it appears to modulate some physiological processes. We have analyzed the catalase levels to investigate the role of antioxidant enzymes against toxic reactive oxygen species in Plasmodium vivax infected patients and compared with healthy controls. The difference between catalase levels of patients was lower than control group and was statistically significant (p < 0.05). In neither the patient nor control group was correlation found between age and catalase levels.